Dari Kanca Wingking hingga Keseimbangan Kosmos: Dinamika Pencitraan Perempuan Jawa di Film Indonesia: From Kanca Wingking to Cosmic Balance: Dynamics of Javanese Women Images on Indonesian Movies - Ela Indah Dwi Syayekti (Besari: Journal of Social and Cultural Studies, 2024)
The development of media undoubtedly has impacts on life in society, including women and Javanese culture. The way media using women and  Javanese culture will unnecessarily shows true images of society compared to the real life happening in society. The study aims to explain how the images of Java women in the media, especially movies, and their comparisons to real life in Java society, with a qualitative approach through library research methods. The results of this research are some movies still showcasing how the patriarchal side of Java culture with women is characterized as a weak figure and serves as a mere kanca wingking. However, some movies have already depicted the values of women's life in Java, in that women not only supporting men but also performing equal roles like men in the public sphere. The role of women is even an extension of their household role so that they do not abandon their duties as wives by taking care of the family. It is expected that this research will give a different insight on the situation of Javanese women in the real life.   Perkembangan media tidak diragukan lagi berdampak pada kehidupan masyarakat, termasuk perempuan dan budaya Jawa. Cara media menampilkan perempuan dan budaya Jawa tidak selalu sesuai dengan kehidupan nyata yang terjadi di masyarakat. Penelitian ini bertujuan untuk menjelaskan bagaimana gambaran perempuan Jawa dalam media, khususnya film, dan perbandingannya dengan kehidupan nyata di masyarakat Jawa, dengan pendekatan kualitatif melalui metode penelitian kepustakaan. Hasil penelitian ini adalah beberapa film masih menampilkan bagaimana sisi patriarki budaya Jawa dengan perempuan dicirikan sebagai sosok yang lemah dan hanya berfungsi sebagai kanca wingking belaka. Namun, beberapa film telah menggambarkan nilai-nilai kehidupan perempuan di Jawa, di mana perempuan tidak hanya mendukung laki-laki tetapi juga memainkan peran yang sama seperti laki-laki di ruang publik. Peran perempuan bahkan merupakan perpanjangan dari peran rumah tangganya sehingga mereka tidak mengabaikan tugasnya sebagai istri dengan mengurus keluarga. Diharapkan penelitian ini akan memberikan wawasan yang berbeda tentang situasi perempuan Jawa dalam kehidupan nyata.